DEVELOPMENT OF ONE PAIR ALL SHAPE FOR PLANE FIGURES MATERIALS IN GRADE VII OF JUNIOR HIGH SCHOOL - Bagus, Satria Tu; Izzati, Nur (Jurnal Pendidikan Matematika dan IPA, 2024)
This research aims to provide a solution to the challenges encountered in learning mathematics, particularly regarding plane figures. This specific area of study necessitates teaching aids that can effectively illustrate plane figures to students. The research primarily focuses on developing a teaching prop that enhances students' comprehension of flat shape materials. The study follows a research and development methodology, which involves product development and quality assessment. For data analysis, descriptive quantitative methods utilizing Sugiyono's descriptive percentage technique are employed to evaluate the product's validity. Based on material and media validation tests, the "One Pair All Shape" prop meets the criteria for both material and form suitability, as assessed by four validators. The material expert validation resulted in an 86.7% rating, while the media expert validation yielded an 84% rating, indicating a very valid category for both aspects.